2019
DOI: 10.15294/sji.v6i2.20585
|View full text |Cite
|
Sign up to set email alerts
|

Software Defined Networks: a Comparative Study and Quality of Services Evaluation

Abstract: Software-Defined Network (SDN) as architecture network that separates the control and forwarding functions, so that network operators and administrators can configure the networks in a simple and centrally between thousands of devices. This study is designed and evaluate the Quality of Services (QoS) performances between the two networks employed SDN-based architecture and without SDN-based. MinNet as a software emulator used as a data plane in the network Software Define Network. In this study, comparison of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
3
0
1
Order By: Relevance
“…Traditional computer networking (N0) recorded the highest bandwidth, while N1 recorded the highest throughput and significant impact on the jitter column. The result corroborated [16] as they observed significant F-value and stability in the SDN application-awareness experiment.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Traditional computer networking (N0) recorded the highest bandwidth, while N1 recorded the highest throughput and significant impact on the jitter column. The result corroborated [16] as they observed significant F-value and stability in the SDN application-awareness experiment.…”
Section: Resultssupporting
confidence: 81%
“…The researchers determined the aspects that enable Software-Defined Networking to provide quality of service features in data networks using network simulation over the same base network and under the same working conditions by carrying out measurements of the packet forwarding response time and management of the transported bandwidth. Nugroho et al [16] reported that the QoS analysis of the Software-Defined Network architecture performed better than conventional traditional network architectures with the value of latency delay on the Software-Defined Network ranging from 0.019ms to 0.084ms, and with 0% packet loss when it addressed network traffics of 10-100Mbps. The authors reported the Quality of Service (QoS) performances between the two networks employing SDN-based architecture and without SDN-based architecture using Mininet as a software emulator.…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate this assessment, the study employs simulation techniques, specifically using the SDN network emulator and the MiniNet Floodlight controller. A range of Quality of Service (QoS) parameters, including latency delay, jitter, throughput, and packet loss, is employed to gauge the QoS metrics of the latter network [19].…”
Section: A Data Collectionmentioning
confidence: 99%
“…Penelitian kelima dilakukan oleh Govindarajan, et al, untuk meneliti QoS Controller pada jaringan SDN Cloud Computing pada studi kasus layanan video streaming [13]. Penelitian keenam dilakukan oleh Nugroho untuk melakukan perbandingan nilai QoS pada jaringan SDN dengan jaringan komputer konvensional [14] Untuk kebutuhan hardware digunakan komputer pribadi dengan spesifikasi: ASUS A456UR Intel(R) Core (TM) i5-6200U CPU @ 2.30GHz (4CPUs), memori DDR4 4096MB, HDD 1TB. Selain itu juga ditambahkan dengan koneksi internet untuk kemudahan penggunaan repositori online.…”
Section: Pendahuluanunclassified